BUILT-IN COARSE GAIN CALIBRATION, RESOLUTION TWO-STEP TDC CMOS BY PULSE-SHRINKING FINE STAGE - VANISREE, K.; SREENIVASULA, MUDE; Y., D.NARESH (International Journal of Psychosocial Rehabilitation, 2020)
This paper suggests a computerized converter (TDC) opportunity that concurrently meets a wide variety of knowledge and fine-time targets. In the second step, the suggested TDC uses beat contracting (PS) plot for a fine target and two-advance (TS) engineering for a wider range. By utilizing an implied counterbalance beat and a balance beat width identification plans, the proposed PS TDC forestalls an undesirable non-uniform contracting rate problem in the conventional PS TDCs. The suggested TS architecture obtains nonlinearity with a few techniques, introducing an implied coarse raise adjustment scheme, owing to the sign spread and extension fraud between coarse and fine phases. In a 0.18-μm normal CMOS invention, the replication results of the TDC modified display 2.0-ps objectives and 16-piece go relative to 130-ns input period interim of 0.08-mm2 area. It runs at 3.3 MS/s with a 1.8-V supply of 18.0 maws and achieves a single-shot precision of 1.44-ps.